2022
DOI: 10.1186/s12992-022-00838-0
|View full text |Cite
|
Sign up to set email alerts
|

International medical electives during and after the COVID-19 pandemic - current state and future scenarios: a narrative review

Abstract: Background International medical electives are an important and popular component of the academic curriculum in many medical schools and universities worldwide. The purpose of abroad electives is to provide medical students with an opportunity to gain a better understanding of education and healthcare in an international context. The COVID-19 pandemic, however, has substantially changed the international elective landscape. Travel restrictions, closures of international elective programs and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 81 publications
0
13
0
Order By: Relevance
“…Although largely from pre-pandemic times, our data may allow for important first insights in motivations for (and barriers to) electives in China. Data from the last 2 years would be most desirable, but is largely unavailable due to COVID-19 related travel restrictions and closure of international elective programs [ 13 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although largely from pre-pandemic times, our data may allow for important first insights in motivations for (and barriers to) electives in China. Data from the last 2 years would be most desirable, but is largely unavailable due to COVID-19 related travel restrictions and closure of international elective programs [ 13 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…International medical electives (IMEs) are pertinent to global health education and allow students to immerse in foreign healthcare system for a short period [ 13 ]. IMEs have been associated with various educational benefits, potentially increasing students’ medical, cultural and linguistic competences [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Globalization has given medical students the opportunity to pursue electives abroad, which may enhance the long-term socialization of medical professionals and foster cross-cultural exchange in a globalized world [ 5 9 ]. Electives also allow students for a global view on health problems of current times in a world where “the separation between domestic and international health problems is no longer useful” (Dr. Brundtland, Director General of the World Health Organization 1998–2003) [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many recent studies have discussed the role of elective courses in undergraduate education (Lumb & Murdoch-Eaton, 2014;Kusurkar & Croiset, 2014;Suzuki & Nishigori 2018;Daccache et al, 2020, Willott et al, 2019, Cherniak et al, 2013. Many studies have reported the benefits of electives like increased knowledge and skills, enhanced critical thinking and problem-solving skills, Improved communication and teamwork skills, increased self-confidence and motivation, a more well-rounded education, opportunity for exploratory learning, lateral thinking, immersive learning, and development of spirit of enquiry (Khilnani & Thaddanee, 2022;Ramalho et al 2020, Al-Taher 2022Stys et al, 2013, Stone at al., 2022Bath et al, 2020, Storz, 2022. Also, electives affect the future choices of students regarding their clinical practice (Alkhaneen et al, 2018;Zuckerman et al, 2016;Dada et al, 2022;Rudasill et al, 2022;Alghamdi et al, 2022;Anand & Sankaran, 2019).…”
Section: Introductionmentioning
confidence: 99%